Networked control systems for intelligent transportation systems and industrial automation - Refaat, Tarek Khaled Salaheldin Ismail (AUC Knowledge Fountain, 2012)
This thesis presents a study of two different applications of Networked Control Systems. The first is: Ethernet Networked Control System On-board of Train-wagons. An Ethernet backbone is shared between control and entertainment. The wagon contains a dedicated control server and a dedicated entertainment server, which act as fault-tolerant machines for one another. In the event of a server failure, the remaining machine can serve both entertainment and/or control. The study aims at enhancing system design in order to maximize the tolerable entertainment load in the event of a control/entertainment server failure, while not causing any control violations. This fault-tolerant system is mathematically analyzed using a performability model to relate failure rates, enhancements and rewards. The model is taken further to test two identical wagons, with a total of four fault-tolerant servers. All possible failure sequences are simulated and a different communication philosophy is tested to further minimize the degradation of the entertainment load supported during the failure of up to three of the four servers. The system is shown to be capable of operating with minimal degradation with one out of four servers. The second is: Wireless Networked Control Systems (WNCS) for Industrial Automation. A WNCS using standard 802.11 and 802.3 protocols for communication is presented. Wireless Interface for Sensors and Actuators (WISA) by ABB is used as a benchmark for comparison. The basic unit is a single workcell, however, there is a need to cascade several cells along a production line. Simulations are conducted and a nontraditional allocation scheme is used to ensure correct operation under the effect of co-channel interference and network congestion. Next, fault-tolerance at the controller level is investigated due to the importance of minimizing downtime resulting from controller failure. Two different techniques of interconnecting neighboring cells are investigated. The study models both a two and three-cell scenario, and all systems show that fault-tolerance is achievable. This is mathematically studied using a performability analysis to relate failure rates with rewards at each failure state. All simulations are conducted on OPNET Network Modeler and results are subjected to a 95% confidence analysis.